Endoscopic study of upper gastrointestinal mucosal lesion in chronic renal failure - Gupta, Manoj; Shende, Atul (International Journal of Research in Medical Sciences, 2017)
Background: Chronic renal failure is a syndrome complex results from progressive and irreversible destruction of nephrons regardless of cause. This diagnosis implies that GFR is known to have been reduced for atleast 3 to 6 months. To study the clinical manifestations and assess the type and prevalence of upper gastrointestinal lesions and to correlate the clinical and biochemical parameters with upper GI mucosal lesion in chronic renal failure patients. Methods: Fifty CRF patients from nephrology and Medicine OPD, admitted in the department of Medicine, M.Y. Hospital, Indore, during January 2002 to April 2003 were studied. A detailed History, clinical examination, Urine Examination, renal Function test, U.S.G. was done and then upper GI Endoscopy was performed. Results: Thirty-six males and fourteen females (n=50) were studied. Most common age group was 41-50 years; commonest GI symptom was Anorexia (100%) and Nausea was present in (94%) of patients and GI bleed was seen in (8%). The common upper GI lesion were gastritis (28%), Oesophagitis (16%) and Duodenitis (12%). No patients had Gastric or Duodenal Ulcers. Majority of patients had creatinine clearance between 5-10 ml /min and most of the patients had duration of disease between 11-20 months. Conclusions: Gastrointestinal symptoms are very frequent in CRF patients. There is a high incidence of inflammatory charges of gastrointestinal mucosa in patients of CRF and chronic uremic patients are not at high risk of developing ulcer disease. There is no correlation of these gastrointestinal symptoms and inflammatory changes with age, sex, severity and duration of disease.